If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(3c + -1) + -3 = 13c + 2 Reorder the terms: 5(-1 + 3c) + -3 = 13c + 2 (-1 * 5 + 3c * 5) + -3 = 13c + 2 (-5 + 15c) + -3 = 13c + 2 Reorder the terms: -5 + -3 + 15c = 13c + 2 Combine like terms: -5 + -3 = -8 -8 + 15c = 13c + 2 Reorder the terms: -8 + 15c = 2 + 13c Solving -8 + 15c = 2 + 13c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-13c' to each side of the equation. -8 + 15c + -13c = 2 + 13c + -13c Combine like terms: 15c + -13c = 2c -8 + 2c = 2 + 13c + -13c Combine like terms: 13c + -13c = 0 -8 + 2c = 2 + 0 -8 + 2c = 2 Add '8' to each side of the equation. -8 + 8 + 2c = 2 + 8 Combine like terms: -8 + 8 = 0 0 + 2c = 2 + 8 2c = 2 + 8 Combine like terms: 2 + 8 = 10 2c = 10 Divide each side by '2'. c = 5 Simplifying c = 5
| 4k+3m=6k-5l | | -5z=60 | | -7(t+8)=7 | | 35-17=3(x-5) | | 4h+2=8.5h | | 22+5y-1=17y-11-4y | | 7e^5(t)=100 | | (8a)(2a^3b)(0)= | | -210=3p-6(1-8p) | | 7e^5t=100 | | 2x^2+23x+86=0 | | 2x^2+21x+50+2x+36=0 | | -7+2(6+7x)=-93 | | 4b+3b-5=16 | | 2x^3+x+9=0 | | 8x+5=3x | | 8t^2=0 | | 8n-(1-4n)=-85 | | 6t^2+37t-35=0 | | v^2-7v+6=0 | | -4.9x^2+80x=0 | | 3x+24=72 | | 9.7=x+4.3 | | 18+x=42 | | 5x^4-80y^4=0 | | 5x^2-45+90=0 | | 5x^4-16y^4=0 | | 252=-r+5(6r+4) | | 12n=84 | | 3m+15=m+30 | | -5a(3a^2-6a)-4(2a^2-4a)=0 | | 27x^3-75xy^2=0 |